Penguatan Karakter Religius Siswa Melalui Kegiatan Keagamaan - Khairul Anam; Sugiono (CV Edujavare Publishing, 2023)
The moral crisis among students, especially junior high school / MTs, is still a problem that must be addressed. The objective to be achieved in this study is to understand and analyze the implementation and impact of religious activities on strengthening the religious character of students in island educational institutions. This research uses a qualitative approach with a type of case study research. Data collection is done by observation, interviews, and documentation. The results of this study are that the form of religious activities in island educational institutions is in the form of Yasin reading, Ratibul ḥaddad recitation, prayer every before and after lessons, Istigasah, Islamic Holiday Commemoration, Haflah Imtihan, Ziaroh, Common Prayer. The impact of religious activities on strengthening the religious character on the aspect of knowledge in the form of student knowledge of activities recommended in religion, knowledge of how to behave and act, knowledge of religious science. In the aspect of feelings, religious activities familiarize students with carrying out activities of a religious nature, become aware of the importance of religion, make students feel bad when committing violations. The aspect of behavior makes students obedient to God, confident, love knowledge, discipline, responsibility, respect others.